Hubungan Antara Pertemanan Dan Dukungan Sosial dengan Kecerdasan Emosi Pada Remaja (Siswa Sekolah Menengah Pertama Di Surakarta) - Yuliasari, Sheylla Bryan, Dra. Wiwien Dinar Prastiti, M.Si (2017)
Teenagers are often regarded as the most emotional stage of development, but the reality is not all emotional. Some of the factors that may affect influence aresocial friendship and support. The purpose of this research is to know: (1) the relationship betweenfriendship and social support with emotional intelligence at SMP Negeri 15 Surakarta Students. (2) the relationship between friendship with emotional intelligence at SMP Negeri 15 Surakarta Students. (3) the relationship between social support and emotional telligence at SMP Negeri 15 Surakarta Students. (4)big contribution of friendship and social support to emotional intelligence at Student SMP Negeri 15 Surakarta. The population in this study is all students of class VII SMP Negeri 15 Surakarta amounted to 250 students with the number of research samples of 60 students, Namely class VII D amounted to 29 students and class VII F amounted to 31 students. The selection of this subject using cluster random sampling technique. Data collection methods in this study using a scale. Techniques analaisis data used multiple regression. Based on data analysis obtained F count equal to 30,553with p <0,05. These results indicate there is a positive and significant relationship between friendship and social support with emotional intelligence in students. Rx1y results of 0.706 with p <0.05 means there is a very significant relationship between friendship with emotional intelligence. The result of rx2y of 0,556 with p <0,05 means there is a very significant relation between social support with emotional intelligence. The effective contribution given by the variable of friendship and social support with emotional intelligence is shown by R = 0,719 or 71,9%. This means there are still 48.3% other factors that affect emotional intelligence in junior high school students